Joint Source-Channel Coding for Wavelet-Based Scalable Video Transmission Using an Adaptive Turbo Code - Ramzan, Naeem; Wan, Shuai; Izquierdo, Ebroul (EURASIP journal on image and video processing, 2007)
An efficient approach for joint source and channel coding is presented. The proposed approach exploits the joint optimization of a wavelet-based scalable video coding framework and a forward error correction method based on turbo codes. The scheme minimizes the reconstructed video distortion at the decoder subject to a constraint on the overall transmission bitrate budget. The minimization is achieved by exploiting the source rate distortion characteristics and the statistics of the available codes. Here, the critical problem of estimating the bit error rate probability in error-prone applications is discussed. Aiming at improving the overall performance of the underlying joint source-channel coding, the combination of the packet size, interleaver, and channel coding rate is optimized using Lagrangian optimization. Experimental results show that the proposed approach outperforms conventional forward error correction techniques at all bit error rates. It also significantly improves the performance of end-to-end scalable video transmission at all channel bit rates.